100 years of flight a chronicle of aerospace history, 1903-2003 - Winter, Frank H.; Van der Linden, F. Robert (American Institute of Aeronautics and Astronautics, 2003)
In just 100 years, air and space exploration has progressed from a 12 second, 120 foot flight by two brothers, to a 30 year sustained flight, now 7 billion miles from Earth, travelling at 300,000 mph. This volume chronicles the most significant accomplishments in aerospace since 1903.